Topically Applied Bacteriophage to Control Multi-Drug Resistant Klebsiella pneumoniae Infected Wound in a Rat Model - Mohamed S. Fayez; Toka A. Hakim; Mona M. Agwa; Mohamed Abdelmoteleb; Rania G. Aly; Nada N. Montaser; Abdallah S. Abdelsattar; Nouran Rezk; Ayman El-Shibiny (MDPI AG, 2021)
(Background): Multi-drug-resistant Klebsiella pneumoniae (MDR-KP) has steadily grown beyond antibiotic control. Wound infection kills many patients each year, due to the entry of multi-drug resistant (MDR) bacterial pathogens into the skin gaps. However, a bacteriophage (phage) is considered to be a potential antibiotic alternative for treating bacterial infections. This research aims at isolating and characterizing a specific phage and evaluate its topical activity against MDR-KP isolated from infected wounds. (Methods): A lytic phage ZCKP8 was isolated by using a clinical isolate KP/15 as a host strain then characterized. Additionally, phage was assessed for its in vitro host range, temperature, ultraviolet (UV), and pH sensitivity. The therapeutic efficiency of phage suspension and a phage-impeded gel vehicle were assessed in vivo against a K. pneumoniae infected wound on a rat model. (Result): The phage produced a clear plaque and was classified as Siphoviridae. The phage inhibited KP/15 growth in vitro in a dose-dependent pattern and it was found to resist high temperature (˂70 °C) and was primarily active at pH 5; moreover, it showed UV stability for 45 min. Phage-treated K. pneumoniae inoculated wounds showed the highest healing efficiency by lowering the infection. The quality of the regenerated skin was evidenced via histological examination compared to the untreated control group. (Conclusions): This research represents the evidence of effective phage therapy against MDR-KP.